PENGARUH TAX AMNESTY, RELIGIUSITAS, DAN NORMA SUBJEKTIF TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA JAKARTA KOJA - Adis Naurah Khansa; Masripah Masripah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
This study aims to determine whether there is influence from the implementation of tax amnesty, religiousity, and subjective norm on individual taxpayer compliance at KPP Pratama Jakarta Koja. This study uses a quantitative method with the sample being individual taxpayers who are registered and active at KPP Pratama Jakarta Setiabudi Dua. The sampling technique used probability sampling with a total sample of 120 respondents. The data is processed and tested using the SEM-PLS method with the SmartPLS 3.0 application. The results of this study indicate that tax amnesty, religiousity, and subjective norm positive effect on individual taxpayer compliance at KPP Pratama Jakarta Koja.